Café Atmosphere, And Quality Service To Increase Customer Loyalty Mediate By Satisfaction - Muhammad Syahrin Asman; Elfitra Desy Surya; Mesra B (International Journal of Management, Economic and Accounting, 2024)
This study aims to explore the influence of café atmosphere and service quality to increase customer loyalty mediated by satisfaction. This research was conducted by quantitative methods with an associative approach. Data analysis was used in this study using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS software version 3 and primary data from 199 respondents who are consumers of Goodfella Cafe. The results showed that the café atmosphere and service quality, have a positive and significant influence on increasing customer loyalty, with customer satisfaction as a mediator. These findings are important for Goodfella Cafe management and other café business owners to improve customer loyalty, and customer experience and strengthen their position in the market. By improving and improving the café atmosphere and service quality, it is hoped that Goodfella Cafe can attract more new customers and retain old customers, thereby increasing sales turnover.